Дмитро Іванович Каченовський – учений-правознавець, педагог-просвітник (за матеріалами діяльності Харківського юридичного товариства) - Малютіна, О. К.; Maliutina, O. K. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 4 (103). - С. 24-35, 2023)
Досліджено наукову та педагогічну діяльність ученого-правознавця, професора Харківського університету Дмитра Івановича Каченовського (1827–1872), який стояв біля витоків вітчизняної юридичної освіти та справив значний вплив на її розвиток. Аналіз історичних джерел (матеріалів, виданих Харківським юридичним товариством з нагоди 30-ї річниці смерті вченого) свідчить, що характерними рисами вченого-правознавця були гуманістичні орієнтири, широта світогляду, різноманітність напрямів наукових пошуків. Природні здібності, академічна освіта, розвинений інтелект, працездатність визначали його особистість. Знання іноземних мов, закордонні стажування, особисті контакти із зарубіжними колегами, вивчення європейської наукової літератури в оригіналах дозволяє охарактеризувати його як типового представника «внутрішнього Заходу», який бачив своє покликання у поширенні освіти, новітніх наукових досягнень. На його лекціях, яким був притаманний комплексний підхід, виховувалося покоління громадських і судових діячів епохи великих реформ.

The article examines the scientific and pedagogical activities of the legal scholar, professor of Kharkiv University Dmytro Ivanovych Kachenovskyi (1827–1872). The researcher pioneered the national legal education and had a significant impact on its development. The study of the creative work of the mid-nineteenth century international law expert became relevant in the early twentieth century. In 1903, Kharkiv Law Society held a solemn meeting on the occasion of the 30th anniversary of Dmytro Kachenovskyi’s death. Following the meeting, a collection of materials in memory of Dmytro Kachenovskyi was published. These materials are a valuable historical source that contain special information and contribute to a deeper study of the scientist’s scientific heritage. The study of the source expands the existing documentary base. The purpose of the study is to study and analyse the materials of the collection published by the Kharkiv Law Society in honour of Professor Kachenovskyi. The analysis of memoirs helps to reconstruct the key episodes of a scientist's life in more detail, to form an idea of his personality, to explore the directions of his scientific research, views on topical social issues, attitude to teaching, relationships with colleagues, and influence on students. It has been proved that the distinctive features of the scientist were humanistic guidelines, breadth of outlook, and diversity of scientific interests. His natural abilities, academic education, developed intellect, and ability to work determined his personality. His knowledge of foreign languages, foreign internships, personal contacts with foreign colleagues, and the study of European scientific literature in the original allows us to characterise him as a typical representative of the “inner West” who saw his mission in spreading education and the latest scientific achievements. His lectures, which were characterised by a comprehensive approach to teaching, brought up a generation of public and judicial figures of the era of great reforms.

Исследована научная и педагогическая деятельность ученого-правоведа, профессора Харьковского университета Дмитрия Ивановича Каченовского (1827–1872), который стоял у истоков отечественного юридического образования и оказал значительное влияние на его развитие. Анализ исторических источников (материалов, выданных Харьковским юридическим обществом по случаю 30-летия смерти ученого) свидетельствует, что характерными чертами ученого-правоведа были гуманистические ориентиры, широта мировоззрения, разнообразие направлений научных изысканий.
Dmytro Ivanovych Kachenovskyi – a legal scholar, educator and teacher (based on the materials of Kharkiv Law Society)
Keywords: Каченовський Д.; учений-правознавець; педагог-просвітник; Харківський університет; Харківське юридичне товариство; Kachenovskyi D.; legal scholar; educator; Kharkiv University; Kharkiv Law Society; Каченовский Д.; ученый-правовед; педагог-просветитель; Харьковский университет; Харьковское юридическое общество